2020
DOI: 10.3390/jcm9020580
|View full text |Cite
|
Sign up to set email alerts
|

Communicating the Risk of Death from Novel Coronavirus Disease (COVID-19)

Abstract: To understand the severity of infection for a given disease, it is common epidemiological practice to estimate the case fatality risk, defined as the risk of death among cases. However, there are three technical obstacles that should be addressed to appropriately measure this risk. First, division of the cumulative number of deaths by that of cases tends to underestimate the actual risk because deaths that will occur have not yet observed, and so the delay in time from illness onset to death must be addressed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
124
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(138 citation statements)
references
References 17 publications
4
124
0
10
Order By: Relevance
“…From a stochastic point of view, such modelling is prone to an exponential propagation of imputation error, which can principally be controlled for and reported with these models 12 . However, as in the present case such error propagation will finally arrive at conclusions via modelling, that are indeed based on assuming merely all or nothing 4 and thus indeed would need to be communicated with uttermost caution to the public and foremost health politicians 5 .…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…From a stochastic point of view, such modelling is prone to an exponential propagation of imputation error, which can principally be controlled for and reported with these models 12 . However, as in the present case such error propagation will finally arrive at conclusions via modelling, that are indeed based on assuming merely all or nothing 4 and thus indeed would need to be communicated with uttermost caution to the public and foremost health politicians 5 .…”
Section: Introductionmentioning
confidence: 82%
“…There is one last question, which I will not discuss here. Provided that there was a defined place with more than 364.000 people, and provided at that place everybody knew what COVID-19 is, will not miss a single death, will take care of people coughing, and provided that there was enough testing capacity at hand: Could it be that my formula (5) to correct for selecting more morbid persons into a test pool, will also correct for all other sorts of selection bias, therefore delivering an ultra-precise early estimate for mortality?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported several clinical characteristics in severe cases and patents with adverse outcomes following COVID-19 infection. Older age, comorbidities such as hypertension, respiratory disease, diabetes, cancer, cardiovascular disease, high LDH level, and lymphocytopenia have all been associated with an increased risk of mortality (4,9,(16)(17)(18). Obesity and smoking have been reported to correlate with increased risks in other studies (4,17).…”
Section: Discussionmentioning
confidence: 99%
“…The global outbreak of severe acute respiratory syndrome coronavirus (SARS-CoV) in 2003 and the more recent coronavirus 2 (SARS-CoV-2) have made it clear that older people, especially those with comorbidities, die more easily from these infections than younger people [1][2][3]. The global spread of the novel coronavirus disease (COVID- 19), and the emerging evidence of a sustained human-to-human transmission, suggest that we are dealing with a historic challenge to our capacity to protect the health of our elderly community.…”
Section: Introductionmentioning
confidence: 99%